2012
DOI: 10.1007/s00535-012-0650-8
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index is the most useful predictive factor for the onset of nonalcoholic fatty liver disease: a community-based retrospective longitudinal cohort study

Abstract: BMI was confirmed as the most useful predictive factor for NAFLD onset in both sexes; its cutoff levels were similar to those recommended by the World Health Organization for helping to prevent metabolic disease. An accurate BMI cutoff level will enable clinicians to identify subjects at risk for NAFLD onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 29 publications
5
56
3
2
Order By: Relevance
“…Although total body adiposity remains a risk factor for type-2-diabetes, 1 dyslipidemia, 2 cardiovascular disease (CVD) 3 and non-alcoholic fatty liver disease (NAFLD), 4 adipose tissue distribution appears to be a more robust predictor of obesityrelated disease risk. Visceral adipose tissue located among various organs including the liver in the intra-abdominal cavity is associated with type-2-diabetes, [5][6][7][8][9] dyslipidemia, [10][11][12] inflammation, increased risk of thrombosis [13][14][15] and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Although total body adiposity remains a risk factor for type-2-diabetes, 1 dyslipidemia, 2 cardiovascular disease (CVD) 3 and non-alcoholic fatty liver disease (NAFLD), 4 adipose tissue distribution appears to be a more robust predictor of obesityrelated disease risk. Visceral adipose tissue located among various organs including the liver in the intra-abdominal cavity is associated with type-2-diabetes, [5][6][7][8][9] dyslipidemia, [10][11][12] inflammation, increased risk of thrombosis [13][14][15] and NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…N onalcoholic fatty liver disease is becoming more common worldwide, possibly because of the increasing incidence of human obesity (24). Nonalcoholic steatohepatitis (NASH) is closely associated with the metabolic complications as a result of overnutrition, including obesity and insulin resistance (22).…”
Section: Introductionmentioning
confidence: 99%
“…The study enrolled 3215 subjects (882 men and 2333 women) and analyzed the individuals after an observation period of 1208 days. 23 Multivariate analyses confirmed that BMI, at baseline, was the most useful factor for predicting NAFLD onset in both sexes (men: OR 1.223; 95% CI 1.138-1.318; P < 0.001; women: OR 1.331; 95% CI 1.263-1.404; P < 0.001) ( ALT, alanine aminotransferase; BMI, body mass index; CI, confidence interval; HbA1c, hemoglobin A1c; HDL-c, high-density lipoprotein-cholesterol; IR, insulin resistance; NAFLD, non-alcoholic fatty liver disease; OR, odds ratio; TG, triglyceride; UA, uric acid.…”
Section: Body Mass Indexmentioning
confidence: 99%